Fostering a Student-Centered Class Throug the Design and Use of Materials (2019)
ABSTRACT: This action research paper reports the outcomes of a project which intended to explore the promotion of a Student-centered Class through the use of materials under characteristics of variety, novelty, appealing content and achievable challenge. This research involves 27-sixth graders of a rural public institution in Rionegro, Antioquia, Colombia. Data for this project derives from teacher’ class journals, students’ reflections, checklist for assessing materials and participants’ focus group. After analyzing the data, findings report that implementing materials enhanced student-centered aspects like encouraging students’ participation in the decision making process; facilitating variety in activities by making language learning comprehensible, amusing and feasible; permitting to work from students’ choice and interest; and promoting group work as a strategy to share with one another and easily getting a mutual result.